1992
DOI: 10.3354/meps090061
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial numbers and activity, microalgal biomass and productivity, and meiofaunal distribution in sediments naturally contaminated with biogenic bromophenols

Abstract: Sediment cores were collected inside and outside of a bed of a bromophenol-producing marine polychaete, Notomastus lobatus, and examined for impact of the bromophenols on sediment microflora and meiofauna around N. lobatus burrows. No significant differences were found between microbial parameters measured inside and outside of the N. lobatus bed. Integrated 6 cm cores taken adjacent to N. lobatus burrows contained 1.2 x 10' bacteria ml-l. Cell numbers were similar at control sites within the bed, but away fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 53 publications
(63 reference statements)
3
41
0
Order By: Relevance
“…Although ammonium oxidation appears especially sensitive to bromophenol inhibition, other aerobic processes, including thymidine uptake, may be relatively insensitive (Steward et al 1992(Steward et al , 1996. Likewise, anaerobic processes such as sulfate reduction appear insensitive to bromophenols, at least at typical ambient concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ammonium oxidation appears especially sensitive to bromophenol inhibition, other aerobic processes, including thymidine uptake, may be relatively insensitive (Steward et al 1992(Steward et al , 1996. Likewise, anaerobic processes such as sulfate reduction appear insensitive to bromophenols, at least at typical ambient concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, 2,4-DBP has enhanced sulfate reduction rates, with only transient inhibition at mM concentrations (King 1988). Slightly higher bacterial densities occur in the burrow wall lining of Stereobalanus canadensis, a 2,4,6-tribromophenol (TBP)-containing enteropneust, than in adjacent sediments, but bacterial cell density, acetate assimilation, microalgal biomass and production, and meiofaunal densities do not differ significantly between bulk sediments and sediments from areas with Notomastus lobatus, a 4-bromophenol (BP)-containing capitellid polychaete (Steward et al 1992). Similarly, no significant differences in microbial biomass and community structure have been noted for burrow sediments of N. lobatus and Branchyoasychus americana, a polychaete that does not contain bromophenols (Steward et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…If the dechlorinase and ring cleavage activities we have demonstrated for Thalassiosira sp. are broadly distributed among diatom and other microalgal species, they may contribute to the resistance of some natural benthic marine algal assemblages to halophenols (Steward et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorinated phenolic compounds, such as chlorophenols, chloroguiacols, and chlorocatechols, have numerous anthropogenic sources, including pulp mill effluent (Kringstad & Linström 1984, Xie et al 1986, Häggblom & Salkinoja-Salonen 1991, agricul-tural and residential runoff (Ahlborg & Thunberg 1980), and sewage and wastewater discharges (Chapman et al 1996). In addition, bromophenolic compounds are natural products of a variety of marine organisms including many species of marine macroalgae (reviews by Butler & Walker 1993, Gribble 1999 and infaunal polychaetes and hemichordates (Woodin et al 1987, Chen et al 1991, Woodin 1991, Steward et al 1992, 1995, Fielman et al 1999, Gribble 1999. These anthropogenic and biogenic phenolic and halophenolic compounds can accumulate to significant levels in surficial sediments (Karickhoff et al 1979, Schellenberg et al 1984, King 1986, Xie et al 1986, Lincoln et al 2002, and at least some of these compounds, at concentrations found in sediments, are demonstrably toxic to some of the sediment biota (Woodin 1991, Woodin et al 1993.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation